Work-life balance: family satisfaction of TVET as human capital investment in Malaysia / Adidinizar Zia, Tan Peck Leong and Geetha Subramaniam - Zia, Adidinizar; Tan, Peck Leong; Subramaniam, Geetha (Faculty of Business and Management, 2022)
Malaysia requires a large group of skilled workers to build, expand and eventually sustain its economic growth to become a high-income country. However, current TVET institutions in Malaysia are far from being able to supply Malaysia with sufficient skilled workers in the future. This may be due to negative perceptions of the public regarding work-life balance and well-being when choosing TVET as a career pathway. Therefore, it is important to determine if TVET jobs are inferior to conventionally educated jobs in terms of family satisfaction, which refers to perceptions of family quality such as solidarity, happiness, and overall relational well-being. In this study, surveys distributed to 160 TVET graduates and 160 conventionally educated graduates are analysed using PLS-SEM analysis and PLS-SEM multigroup analysis. SmartPLS software version 3.2.7 was used for this research. The findings show that TVET jobs are no worse than conventionally educated graduates jobs in terms of family satisfaction.